Long walk to freedom - Mandela, Nelson, 1918-2013; Van Wyk, Chris; Bouma, Paddy; Mandela, Nelson, 1918-2013. (London : Macmillan Children's Books, 2014)
"Let freedom reign" Read the amazing story of a true hero of our times and discover how a little boy whose father called him "troublemaker" grew up to fight apartheid, became South Africa's first black president and campaign for freedom and justice throughout the world.
This abridged edition first published: 2009.
"Abridged from the book Long walk to freedom by Nelson Mandela, first published 1995."--Colophon.
With a special foreword from his close friend, Archbishop Desmond Tutu.
Keywords: Mandela, Nelson, -- 1918-2013 -- Juvenile literature; Presidents -- South Africa -- Biography -- Juvenile literature; South Africa -- Politics and government -- 20th century -- Juvenile literature